Supporting 7th Grade Students’ Understanding of Angles using Central Java Traditional House - Hartono, Hartono; Nursyahidah, Farida (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
Angle is one of the important materials to be studied because it is basic in learning geometry and many applications in life. However, students still have difficulty in learning angles. Therefore, it is necessary to design learning with the right context and approach to overcome the difficulties. This study aims to produce a learning trajectory that will help students for understanding angles. The activities were designed based on IRME with Joglo Traditional house context as the starting point. A design research method is used has three stages: preparing for the experiment, design experiment, and retrospective analysis. This study’s subjects were 6 students from SMP Negeri 1 Juwana with different abilities: high, medium, and low abilities. The result of this study was Learning Trajectory which consists of learning processes in four activities: observing the video of the joglo traditional house for understanding the concept of angles, drawing and measuring the angles; categorizing the angles types; solve contextual problems related to angles. In this study, the design experiment stage was limited to the pilot experiment stage. This study shows that learning design using the context of a traditional house can help students to understand the angle and can be an inspiration to explore local wisdom to introduce mathematics topics.Sudut merupakan salah satu materi yang penting dipelajari karena merupakan dasar dalam pembelajaran geometri dan juga banyak aplikasinya dalam kehidupan. Namun, siswa masih mengalami kesulitan dalam mempelajari sudut. Oleh karena itu, perlu dirancang pembelajaran sudut dengan konteks dan pendekatan yang tepat untuk mengatasi kesulitan tersebut. Penelitian ini bertujuan menghasilkan lintasan belajar yang membantu siswa dalam memahami sudut. Semua kegiatan didesain berbasis PMRI dengan konteks rumah adat joglo sebagai starting point. Metode design research digunakan terdiri dari tiga tahapan yaitu preparing for the experiment, design experiment, dan retrospective analysis. Subjek dari penelitian ini adalah 6 siswa dari SMP Negeri 1 Juwana dengan kemampuan yang berbeda yaitu kemampuan tinggi, sedang, dan rendah. Hasil dari penelitian adalah lintasan belajar yang terdiri dari serangkaian proses pembelajaran dalam empat aktivitas yaitu mengamati video rumah adat joglo untuk memahami konsep sudut, menggambar dan mengukur besar sudut; mengkategorikan jenis-jenis sudut; dan menyelesaikan masalah kontekstual yang berkaitan dengan sudut. Pada penelitian ini, tahapan design experiment hanya terbatas tahap ujicoba pilot. Penelitian ini menunjukkan bahwa pembelajaran dengan konteks rumah adat membantu siswa untuk memahami sudut dan dapat menjadi inspirasi untuk menggali kearifan lokal untuk memperkenalkan topik matematika.